Pattern and Management of Hypospadias Among Children in a Tertiary Care Hospital (Journal of Paediatric Surgeons of Bangladesh, 2026)
Background: Hypospadias is one of the most common congenital anomalies of the male external genitalia, with wide geographical variation in anatomical patterns and surgical approaches. Optimal management remains challenging in resource-limited settings where delayed presentation and limited subspecialty care are prevalent. Objective: To evaluate the clinical patterns, surgical techniques, and early postoperative outcomes of hypospadias repair among children treated at a tertiary care hospital in Bangladesh. Methods: This prospective cohort study was conducted in the Department of Pediatric Urology, Bangladesh Medical University (BMU), Dhaka, Bangladesh, from January 2023 to December 2025. A total of 153 children with hypospadias were enrolled using purposive sampling. Data on anatomical type, associated anomalies, surgical procedures, and complications were recorded. Analysis was performed using SPSS version 26.0. Results: The mean age at surgery was 3.8±2.1 years. Distal hypospadias was observed in 89 patients (58.2%), midshaft in 41 (26.8%), and proximal in 23 (15.0%). Chordee was present in 47 patients (30.7%). The most common repairs were tabularized incised plate (TIP) urethroplasty (60.1%), followed by onlay island flap (23.5%) and two-stage repair (16.4%). Overall complication rate was 21.6%, with urethrocutaneous fistula (9.8%) and meatal stenosis (6.5%) being the most frequent. Complications were significantly higher in proximal hypospadias compared to distal types (34.8% vs. 16.9%, p=0.03). Conclusion: Distal hypospadias predominated in this cohort, and TIP urethroplasty was the most frequently performed procedure. Proximal variants carried higher complication rates, emphasizing the need for specialized surgical expertise and long-term follow-up.Journal of Paediatric Surgeons of Bangladesh (2026) Vol. 17 (1): 19-23